Relating Neuroticism to Emotional Exhaustion: A Dynamic Approach to Personality - Sosnowska, Joanna; De Fruyt, Filip; Hofmans, Joeri (Frontiers in Psychology, 2019)
We build on a novel model of personality [PersDyn] that captures three sources of individual differences (here applied to neuroticism): (1) the average level of neuroticism [baseline], (2) the extent to which people experience different neuroticism levels [variability], and (3) the swiftness with which they return to their neuroticism baseline once they deviated from it [attractor strength]. To illustrate the model, we apply the PersDyn model to the study of the relationship between neuroticism and emotional exhaustion. In the first study we conducted a five-day experience sampling study on 89 employees asked to report their level of state neuroticism six times per day. We found that higher levels of baseline neuroticism and variability were related to increased emotional exhaustion. Furthermore, we found an interaction effect between homebase and attractor strength: people with a high baseline and high attractor strength tend to experience a high degree of emotional exhaustion, whereas people with low levels of baseline neuroticism are less likely to suffer from exhaustion if their attractor strength is high. In the second study we conducted a laboratory experiment on 163 participants, in which we manipulated state neuroticism via short movie clips. The results were similar to the results from study 1. It is concluded that a dynamic approach to individual differences is important in understanding personality.